Your attitude determines your future - Lee, Khai Loon (Penerbit UMP, 2020)
A PhD journey has been one of the greatest achievements in my life. It was not tough but full of boundless challenges. Therefore, in the three years of PhD study, I was not only gaining knowledge and a PhD degree but also life experiences in many aspects. It can be viewed from internal and external factors. Everybody has inimitable experiences and unique expectation towards the journey. The most important is “you need to know what you want”. The sharing in my writing might not be the same with others but it is the real experiences that I had from the journey. Hope it can be one of the positive guidance for your PhD study.